Characterization and Evaluation of Silver Concentrations in Hydroxyapatite Powders - Néstor Méndez-Lozano; Miguel Apatiga-Castro; Alvaro de Jesús Ruíz-Baltazar; Miguel de la Luz-Asunción; Eduardo E. Pérez-Ramírez (Journal of Functional Biomaterials, 2023)
The goal of this study is to evaluate the influence of the concentration of silver on the structural and antimicrobial in vitro properties of silver-doped hydroxyapatite powders obtained using the precipitation method. Different concentrations of silver were evaluated to assess the antimicrobial properties. X-ray diffraction (XRD), Fourier transform infrared spectroscopy (FTIR), Raman spectroscopy, scanning electron microscopy (SEM), and dispersive energy spectroscopy (EDS) were used to characterize the powders. XRD and FTIR showed that the hydroxyapatite structure is not affected by the incorporation of silver; on the other hand, EDS showed the presence of silver in the powders. Antibacterial studies showed the efficiency of hydroxyapatite powders in inhibiting bacterial growth as silver concentration increases. According to the results, silver-doped hydroxyapatite powders are suggested for use in the prevention and treatment of infections in bone and dental tissues.